PERBEDAAN KADAR HEMOGLOBIN SEBELUM DAN SESUDAH PEMBERIAN TABLET FE PADA MAHASISWI STIKES MITRA ADIGUNA PALEMBANG TAHUN 2021 - Untari Anggeni; Cindy Anggraini (LPPM STIKes Mitra Adiguna, 2022)
Giving iron folate supplements regularly to anemia sufferers for a certain period to increase the patient's hemoglobin level quickly. With better iron intake, the child's hemoglobin level will increase. The purpose of this research was to determine the difference in hemoglobin levels before and after administration of Fe tablets to female students of STIKES Mitra Adiguna Palembang in 2021. The scope of this research is the field of obstetrics and reproductive health in adolescents. The design of this research is an analytic survey with a cohort design or often referred to as prospective research. The sample of this research is the 3rd grade DIII Midwifery student of STIKES Mitra Adiguna Palembang, totaling 28 people. The results obtained from the Paired Test statistical test obtained a p value = 0.000, meaning that at alpha 5% there was a difference in hemoglobin levels before and after giving Fe tablets to STIKES Mitra Adiguna Palembang students in 2021. Suggestions to health workers, can work together with the school, to conducting routine checks on hemoglobin levels and giving Fe tablets to female students or students who are teenagers and experiencing menarche.